Pemanfaatan Website Sebagai Media Promosi Pada Simpodial Bali Bambu - Saputra, I Made Arya Budhi; Gautama, I Made Bhaskara; Septian, Putu Ricky Teddy; Yuana, Putu Shakila Ayunia; Sari, Ni Made Wirastika (Indonesian Journal Publisher, 2022)
Simpodial Bali Bambu is a company that uses laminated bamboo as a furniture base. The company is located in Banjar Dinas Bengkel, West Selemadeg, Tabanan Regency, Bali. Through previous research, this effort uses a lamination technique to avoid powder lice, which is the main enemy of bamboo. Laminate itself is a transparent layer and is useful for protecting bamboo so that it is resistant to water, dust mites, and sunlight. A number of products that have been made by this business include chairs, tables and parquet from laminated bamboo. However, this company has problems selling its products. In addition, the management of financial transactions related to the company is still not structured so that the company's profit and loss is not clear. This community service activity aims to overcome partner problems, namely by providing a website as a promotional and educational media about laminated bamboo, providing website management training, and providing training to manage company finances using Microsoft Excel. Monitoring is done by monitoring the development of traffic on the website. Based on the evaluation results, this activity has a satisfaction index of 80.81% with a very good interpretation of the results.